Clinical Spectrum of Oesophageal Strictures in Paediatric Population in North India: A tertiary care experience - Javid , Waseem; Baba, Muneer Ahmad; Kadla, Showkat Ahmad; Shah, Nisar Ahmad (Journal of Neonatal Surgery, 2025)
Background: Oesophageal strictures in children can result from a range of congenital, acquired, or iatrogenic causes. Understanding the causes, clinical presentation, and management outcomes in a specific geographic region like the Kashmir Valley is essential for developing region-specific strategies. Objectives: To assess the spectrum, causes, clinical presentation, and management outcomes of oesophageal strictures in paediatric patients in the Kashmir Valley. Methods: This observational study was conducted at a tertiary care centre in Kashmir and included paediatric patients (0–18 years) diagnosed with oesophageal strictures over three year period from December 2020 to December 2023. Data on demographics, clinical features, imaging, endoscopic findings, aetiology, treatment modalities, and outcomes were collected and analysed. Results: A total of 30 paediatric patients were included, mean age at presentation was 6.2±3 years with male predominance (63.3% ).The most common cause of oesophageal stricture was corrosive ingestion (56.7%), followed by post-surgical/anastomotic strictures (16.7%), peptic strictures due to gastro-oesophageal reflux (13.3%) and congenital anomalies (13.3%). Dysphagia and weight loss were the predominant presenting symptoms. All patients were diagnosed by endoscopy (EGD) Management included endoscopic dilatation (28/30) while surgical interventions were required in (6/30) mostly in refractory strictures. Most patients responded well to endoscopic management 24/30(80%) with 6/30(20 %) requiring surgical correction. Complications occurred in 2 patients including post dilatation perforation and post SEMS placement intolerance . Conclusion: Corrosive ingestion remains the leading cause of oesophageal strictures in children in the Kashmir Valley, highlighting the need for community education and prevention strategies. Early diagnosis and multidisciplinary management can lead to favourable outcomes.